Level of Adequate Knowledge of Non-communicable Diseases and Associated Factors Among Adult Residents of North Shewa Zone, Oromia Region, Ethiopia: A Mixed-Method Approach - Legesse, Elsabeth; Nigussie, Tadesse; Girma, Derara; Geleta, Leta Adugna; Dejene, Hiwot; Deriba, Berhanu Senbeta; Geleta, Tinsae Abeya; Sahlu, Degemu; Tesema, Mengistu; Tilahun, Ayele; Awol, Mukemil; Teshome, Firanbon; et al. (Frontiers in Public Health, 2022)
Background: Noncommunicable diseases (NCDs) are currently the leading cause of morbidity and mortality, posing significant challenges to global healthcare systems. Particularly, the prevalence of NCDs is rising in Ethiopia, resulting in a triple burden of diseases on the health system that disproportionately affects all age groups. Hence, this study aims to determine the level of adequate knowledge of NCDs and associated factors among adult residents of the North Shewa zone, Oromia region, Ethiopia. Methods: A community-based cross-sectional study with a concurrent mixed-method approach was conducted from April 1, 2021 to May 30, 2021 among 846 residents using the multistage sampling technique. Interviewer administered questionnaire was used to collect quantitative data and a guiding checklist was used to collect qualitative data. Bivariable and multivariable logistic regressions were fitted to compute the association between explanatory variables and knowledge of NCDs. Adjusted odds ratios at 95% confidence interval with a p-value < 0.05 were used to decree statistical significance in multivariable analysis. Also, a thematic framework analysis was used for qualitative data analysis. Results: A total of 823 subjects have participated in this study making a response rate of 97.3%. The level of adequate knowledge was 33.9% (95%CI: 30.67, 37.13). Higher-income, receiving information from health professionals, owning a TV, having a family member with NCD(s), and marital status were factors significantly associated with adequate knowledge of NCDs. Conclusion: This study reveals a high level of inadequate knowledge of NCDs despite its foundational ability in tackling the burden of NCDs. As a result, broadening a wider and more comprehensive health promotion strategy for the prevention of triple burden of NCDs would benefit the population. Additionally, special efforts are needed both at the practice and policy levels targeting the disadvantaged groups, such as low-income people, those who do not receive information from health professionals, those who do not own a television, and those who are widowed/divorced, who were found to have less knowledge of NCDs.